Prevalence and spectrum of haemoglobinopathies in females of reproductive age group- A first tertiary care center experience in Punjab, North India - Vikram Narang; Anshul Jain; Sumit Grover; Ankita Soni; Monika Narang; Ashima Taneja (Indian Journal of Pathology and Microbiology)
Background: Thalassemia and hemoglobinopathies are a group of inherited conditions characterized by abnormalities in the synthesis or structure of hemoglobin (Hb). According to estimates, approximately 7% of the world population is a carrier of Hb disorders, leading to high morbidity and mortality. To reduce the burden of these highly prevalent monogenic disorders, detecting them in the carrier stage is crucial to prevent disease progression. Aim: We aimed to estimate the prevalence and spectrum of hemoglobinopathies in females in the reproductive (20–40 years) age group. Settings and Design: It was a retrospective observational study carried out for 2.5 years (from January 2018 till June 2020). Materials and Methods: All the females in the age group of 20–40 years age whose blood samples were received in the department for High-Performance Liquid Chromatography (HPLC) were included. The cases with abnormal HPLC findings were analyzed for hematological parameters including hemoglobin, RBC count, and RBC indices [mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), & red cell distribution width - coefficient of variation (RDW-CV)]. Statistical Analysis: Statistical package for social science (SPSS) statistics 21 version for Microsoft Windows (Chicago, USA) was used for statistical analysis of data. The data were described in terms of range, mean ± standard deviation (SD), frequencies (number of cases), and relative frequencies (percentage) as appropriate. Results: During the study period, 72.2% of the females were affected with β-thalassemia trait, followed by HbD Punjab trait (17.8%), HbQ India trait (2.9%), β-thalassemia major (1.8%), and two cases (1.2%) each of HbS trait, HbD Iran trait, and compound heterozygous of HbD Punjab and β-thalassaemia, whereas HbE trait, compound heterozygous of HbQ and β-thalassemia, compound heterozygous of HbJ-variant and β-thalassemia had one case each (0.6%). Conclusion: Preventive strategies are cost-effective and include population screening, premarital screening, screening of spouses, genetic counseling, and prenatal diagnosis. Educating the carrier females about the potential risk and various screening methods may help in controlling the disease.